Prevalence of Intestinal Parasitic Infection and Malnutrition in Enugu Urban and Suburban Area - Unachukwu, Marian; Nwakanma, Chioma (International Journal of Medical Research and Review, 2014)
Introduction: The prevalence of intestinal parasitic infections and malnutrition among school children in urban and suburban of Enugu metropolis was carried out. Methods: Anthropometric measurements consisting of weight, head circumference and mid arm circumference were measured. Weight for age, head and mid arm circumference were used as indicators to determine the nutritional status (malnutrition). Examination of stool specimens was done using direct wet mount examination and concentration techniques .The parasitosis and malnutrition was studied in 98 (40 urban and 58 suburban) school children aged 1 to 12 years. Results: The overall prevalence (positive) of intestinal parasites in this study was 38(38.8%), while 60(61.2%) were absent (negative). The prevalence of infection was significantly higher among the suburban (%) children than among the urban (%) children. The prevalence of Ascaris lumbricoides 11(27.5%) was higher in suburban than in urban Ascaris lumbricoides 5(12.5%) than all other parasites encountered from suburban and urban area respectively. The study does not really show a significant association between nutritional indicators and intestinal parasitic infection but shows a slight association to Ascariasis and hookworm infection. Conclusion: This study shows that there is a slight improvement in the level of malnutrition, hygiene and sanitation in Enugu metropolis. Since intestinal parasitic infections are associated with malnutrition, controlling these parasites would increase the physical development and well-being of the affected children.